Improving the peri‐operative pathway of people with diabetes undergoing elective surgery: the IP3D project. Issue 12 (13th May 2020) - Page, E.; Allen, R.; Wensley, F.; Rayman, G.
Abstract: Aim: To determine whether outcomes for people with diabetes undergoing elective surgery improve following the introduction of innovations in the peri‐operative care pathway. Methods: Following a baseline audit of 185 people with diabetes listed for elective surgery (July to December 2017) with a length of stay > 24 hours, a number of changes in practice were implemented. These included dissemination of a 'diabetes peri‐operative passport' to participants preoperatively, formation of a diabetes surgery working group, recruitment of surgical diabetes champions and the roll‐out of surgical diabetes study days. Crucial was recruitment of a diabetes peri‐operative nurse, whose role included engaging and educating others and supporting individuals throughout their peri‐operative diabetes care. Records of 166 individuals listed for surgery during the implementation period (July to December 2018) were then audited using the same methodology. Results: The availability of a recent HbA1c measurement significantly increased (63% vs 92%; P ≤ 0.001). The mean HbA1c of those seen for optimizations by the diabetes peri‐operative nurse significantly decreased [84 mmol/mol (9.8%) vs 62 mmol/mol (7.8%); P ≤ 0.001]. Recurrent hypoglycaemia significantly decreased (7.0% vs 0.6%; P = 0.002) and the mean number of hyperglycaemic events in people experiencing hyperglycaemia almost halved (3.0 vs 1.7; P =0.007). The mean length of hospital stay significantly decreased (4.8 vs 3.3 days; P =0.001) and, crucially, 30‐day readmissions did not increase (12% vs 9%; P =0.307). Postoperative complications significantly decreased (28% vs 16%; P =0.008), including a composite of dysglycaemic complications, poor wound healing, wound infection and other infections (12% vs 5.4%; P =0.023). Conclusion: The new pathway improved important peri‐operative outcomes for people with diabetes undergoing elective surgery with the potential for cost savings. These findings could have important implications for peri‐operative care on a wider scale. What's new?: A whole‐pathway approach was developed and implemented in our Trust to improve the outcomes of people with diabetes undergoing elective surgery The pathway used a number of innovative interventions including the dissemination of a 'diabetes peri‐operative passport' to individuals preoperatively, the formation of a diabetes surgery working group, and roll‐out of surgical diabetes study days. Crucial was the recruitment of a diabetes peri‐operative nurse, whose role included engaging and educating others and supporting people with diabetes throughout their peri‐operative journey. The results demonstrate important benefits in many aspects of peri‐operative diabetes care, with the potential for wider adoption by other National Health Service trusts.